RLBM model: modeling of Manet’s routing protocols based on restoration links break - Abdoly, Zahra; Mirabedini, Seyyed Javad; Arebi, Peyman (Journal of Advanced Computer Science & Technology, 2014)
Mobile ad hoc network is a temporary network that consists of a set of mobile nodes with wireless communication. There are several problems in the relationship between the components of these networks. Some of these problems are related to the routing problem. The main challenge in routing protocols of mobile ad hoc networks is links break phenomenon. This phenomenon has many negative impacts on the performance of routing protocols. In this paper, we attempted to study 10 routing protocols in mobile ad hoc networks that try to improve the performance of standard protocols of this type of network using the Restoration Links Break. By studying the behavior of these protocols, a common model used by all these protocols was introduced as Restoration Links Break model. Then the performance of each of the protocols was described based on the proposed model. On the other hand, we divided them into two categories according to protocol functions in Restoration Links Break. First category provides alternate routes before the Links Break event and the second category performs the replacement of route after the links break. Finally, the simulation of results revealed that the first category of protocols has a better delivery rate than the second category but the routing overhead of the second category is less than the first category. Keywords: Mobile ADHOC Network, Routing Protocols, Restoration Links Break, Transmission.